Iron Intake and Supplement Adherence as Determinants of Anemia in Pregnancy: A Literature Review - Frisca Anggraeni Manik; Irfansyah Baharuddin Pakki (Mulawarman International Conference on Tropical Public Health, 2025)
Background : : Anemia in pregnancy remains a critical global health problem, especially in low- and middle-income countries where nutritional deficiencies and limited access to health services persist. Iron deficiency is the leading cause, mainly due to inadequate dietary intake and poor adherence to iron supplementation. Objective : This review aimed to analyze the relationship between dietary iron intake, supplement adherence, and anemia prevalence among pregnant women. Research Methods/ Implementation Methods : A narrative literature review was conducted using databases including PubMed, ScienceDirect, Scopus, Google Scholar, and DOAJ. Articles published from 2020 to 2025 were identified using keywords such as “anemia in pregnancy”, “iron deficiency”, “iron supplementation”, and “adherence”. Inclusion criteria comprised peer-reviewed studies involving pregnant women and examining dietary iron intake or supplement adherence in relation to anemia. Results : Findings indicate that low consumption of iron-rich foods and poor adherence to supplementation are major determinants of anemia. Barriers include gastrointestinal side effects, cultural food taboos, limited awareness, and lack of counseling. Education, family support, and healthcare engagement significantly enhance adherence and hemoglobin outcomes. Conclusion/Lesson Learned : Combining nutrition education with consistent supplementation effectively reduces anemia prevalence. Integrated, community-based strategies are essential to improving maternal iron status and pregnancy outcomes.